DAMAGE AND SHORTCOMINGS OF REINFORCED CONCRETE OUTDOOR POOLS DURING CONSTRUCTION AND LONG-TERM OPERATION - Luchko Й.; Nazarevych Б.; Hashchuk Ю. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
This paper addresses the issues related to the destruction of reinforced concrete monolithic structures in outdoor swimming pools during both construction and long-term operation, drawing upon scientific literature and field studies. The authors analyze various works concerning the destruction of reinforced concrete structures and outline the objectives of this study. General information regarding the construction and long-term operation of new swimming pools is provided. Notably, the paper presents the design of monolithic reinforced concrete pool structures and their reinforcement, illustrated in Figures 1-4. The study also examines the causes and impact of waterproofing issues on the destruction of outdoor swimming pools. Examples of long-term operational open pools are discussed, alongside the results of inspections and instrumental studies of the monolithic walls and floor slabs of long-term swimming pools located in Sokilnyky and the Sykhiv massif in Lviv. One of the research objectives was to assess the current technical condition of the pool structures and determine the feasibility of their continued reliable operation. The study identifies the main reasons for the investigation and proposes solutions to address defects, damage, and challenges associated with long-term operation. Data on the defects and damages that have developed over time due to unfavorable operating conditions are presented. According to current standards, the overall technical condition of the pools is evaluated, and relevant conclusions regarding necessary repair work are drawn. The paper highlights its scientific novelty and practical significance. Based on the survey results and related calculations, proposals for repairs and mitigation of identified shortcomings and damages are developed, accompanied by relevant conclusions.